(untitled) (Olhar de Professor, 2022)
This article aims to identify teachers’ perceptions about challenges and possibilities that the COVID-19 pandemic has imposed on their pedagogical work. The research participants are teachers that work at a private school located in the city of Ponta Grossa, Paraná (Brazil). The research is qualitative and can be categorized as a case study. The data were collected through a questionnaire applied via Google Forms platform, and then analyzed, organized, and categorized based on Content Analysis, wherewith five categories related to difficulties and challenges faced by teachers during the pandemic period were identified. The results point to some difficulties faced by teachers, mainly in the daily work routine, regarding remote teaching. On the other hand, they point to a construction of knowledge about differentiated and motivating methodologies that can also be developed and used in post-pandemic teaching.